Hemorrhagic Post Partum: Syok Hemorrhagic ec Late Hemorrhagic Post Partum - Desti Nur Ayu Ramadhani; Endah Luqmanasari (Jurnal Kebidanan Manna, 2022)
Postpartum hemorrhage is the leading cause of maternal death in developing countries and the primary cause of nearly a quarter of all maternal deaths globally. Postpartum hemorrhage is bleeding that occurs after parturition (delivery), as much as 500 ml in vaginal delivery or more than 1000 ml in cesarean section. Primary postpartum hemorrhage is caused by 4Ts, namely uterine atony (Tonus), retained placenta and blood clots (tissue), birth canal lesions/tears (Trauma), and blood clotting disorders (Thrombin).The purpose of the study was to provide midwifery care for post partum mothers with late HPP through a comprehensive approach to Varney's midwifery care management mindset. The method used is a case study to explore the problem. The research subject is Ny. R P2002 conducted in June 2022, at Amelia Hospital. Data collection techniques include primary data including physical examination, interviews, observation and secondary data, including documentation studies and literature studies. Data analysis was carried out by making narratives from the results of interviews and examinations using 7 Varney steps.Patients are observed and given care in accordance with the authority of the midwife in the hospital who prioritizes collaborative care and then independent care, and from the care provided the differences and gaps between theory and practice are discussed. The conclusion of this study is that there is no gap between theory and practice in midwifery care for Ny. R.